RESTRAINED SECURE DOMINATION IN THE JOIN AND CORONA OF GRAPHS - Enriquez, Enrico Limbo (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
Let be a connected simple graph. A restrained dominating set of a graph , is a restrained secure dominating set of if for each , there exists such that and the set is a dominating set of . The minimum cardinality of a restrained secure dominating set of , denoted by is called the restrained secure domination number of . A restrained secure dominating set of cardinality is called a - of . In this paper, we show that every integer and with is realizable as restrained secure domination number and order of respectively. Further, we characterize the restrained secure dominating sets in the join and corona of two graphs and give some important results.